Semi-Dirac Fermions in a Topological Metal - Yinming Shao; Seongphill Moon; A. N. Rudenko; Jie Wang; Jonah Herzog-Arbeitman; Mykhaylo Ozerov; David Graf; Zhiyuan Sun; Raquel Queiroz; Seng Huat Lee; Yanglin Zhu; Zhiqiang Mao; et al. (Physical Review X)
Topological semimetals with massless Dirac and Weyl fermions represent the forefront of quantum materials research. In two dimensions, a peculiar class of fermions that are massless in one direction and massive in the perpendicular direction was predicted 16 years ago. These highly exotic quasiparticles—the semi-Dirac fermions—ignited intense theoretical and experimental interest but remain undetected. Using magneto-optical spectroscopy, we demonstrate the defining feature of semi-Dirac fermions—B^{2/3} scaling of Landau levels—in a prototypical nodal-line metal ZrSiS. In topological metals, including ZrSiS, nodal lines extend the band degeneracies from isolated points to lines, loops, or even chains in the momentum space. With ab initio calculations and theoretical modeling, we pinpoint the observed semi-Dirac spectrum to the crossing points of nodal lines in ZrSiS. Crossing nodal lines exhibit a continuum absorption spectrum but with singularities that scale as B^{2/3} at the crossing. Our work sheds light on the hidden quasiparticles emerging from the intricate topology of crossing nodal lines and highlights the potential to explore quantum geometry with linear optical responses.